Nuclear Overhauser effect in specifically deuterated macromolecules: NMR assay for unusual base pairing in transfer RNA. - Sánchez, V (1980)
We demonstrate a fairly general method for identification of NMR absorption lines of macromolecues extracted from microorganisms, based on nuclear Overhauser effects (NOE). Several NOE in tRNA are observable between resolved imino proton resonances and ring carbon resonances that are either C(2) protons of adenine or C(8) protons of adenine or guanine. Yeast tRNAPhe was deuterated at the purine C(8) positins by heating in 2H2O and also biosynthetically. NOE between imino protons and adenine C(2) protons of standard A . U base pairs would not be affected by such a label, but some other NOE that might be otherwise similar, such as those of reverse Hoogsteen base pairs, should disappear. Six NOE were shown to be from standard A . U pairs by their nondisappearance. Four NOE from methyl resonances to aromatic proton resonances did disappear. The results disagree with previous assignments based on ring-current theories of imino proton NMR shifts.